AN ANALYSIS OF THE ROLES OF PARENTS IN CHILDREN’S WILLINGNESS TO LEARN ONLINE FROM HOME DURING THE COVID-19 PANDEMIC - Lili Putri; IGA Widari (STKIP Paracendekia NW Sumbawa, 2023)
On March 2020, the Corona Virus (Covid-19) identified as global pandemic. This type of virus infects the human respiratory. In responding to this urgent situation, the Indonesian government implemented online learning. The research aims to determine the roles of parents on Children’s willingness to learn online from home during the Covid-19 pandemic. This research used qualitative method. The participants in this research were 8 parents and 8 students. The research data were obtained from observations and interviews. The result of the study indicates that the role of parents is very important in supporting children’s willingness to learn online from home. Parents who given more responsibility to their children will increase the willingness to learn and the students can reach certain stages in achieving the desire goals in learning. In addition, the researcher found 4 categories namely as a parents, teacher, facilitator and motivator.